Streamlining the operations of the digital partnerships and fintech team of Sun Life Philippines through Trello - Alfonso, Janice M. (Animo Repository, 2022)
This action research streamlined the operations of the Digital Partnerships and Fintech team of Sun Life Philippines through the introduction of a tool to consolidate the projects and activities as well as to foster better collaboration and communication among the members. The pandemic has paved the way for organizations, insurance companies included, to make unprecedented changes in their processes and way of working to continue operating. Virtual work arrangements were implemented and this highlighted the need for employees to be equipped with tools, technology and skills to maintain productivity. Tasked to enable the company digitally, the Digital Partnerships and Fintech team needed to deliver projects and future-proof solutions. The challenges of a remote work set-up coupled with the team’s lack of an established system of collaboration and managing its operations have resulted to missed deadlines and incomplete tasks. Projects were not delivered on time. Through the various tools and methodology of action research and systems analysis, the action researchers have agreed to use a project management tool (Trello) to create a consolidated view of the team’s projects and deliverables. The Project Management Framework and Lewin’s Change Management Framework were used to guide the researchers in the implementation of each cycle. For the first cycle, the boards for each workstream were set-up and a process for virtual communication were established. The consolidated view of the deliverables has helped the team become more organized in the performance of the tasks. Seeing the completed tasks and the extent of the work done have also provided the team with a sense of accomplishment and the motivation to continue working for the achievement of the set goals. The second cycle addressed the uncovered areas for improvement. Separate boards showing the project view were created and labels were standardized. A board compiling the completed task per team member was also implemented. These helped in the monitoring and in updating the team of the deliverables and recent developments, especially when a team member resigned. The action research resulted in a humanized Project Management Framework which can guide teams in employing a balance of scientific methods and humanistic elements in managing projects. Organizations could learn from the exercise and use the results of the study as reference in implementing a system of managing operations especially in a work from home set-up.